Кінетика взаємодії цибаланового барвника з ацетилсукцинатом целюлози - Раєвська, Л. П.; Влязло, Р. Й.; Сидоров, Ю. І.; Єлагін, Г. І (Видавництво Національного університету «Львівська політехніка», 2003)
Вивчено кінетику взаємодії цибаланового барвника “синій” з ацетилсукцинатом целюлози. Встановлено, що процес має складний характер: при низьких температурах він, ускладнений процесом хемосорбції, послаблюється і реакція наближається до першого порядку за барвником. Встановлено, що оптимальним середовищем, в якому проводиться процес, є ацетон. Is investigated kinetic of interaction cybalan of dye "dark blue" with acetilsukcinat of cellulose. Is established, that process carries complex character: for want of low temperatures it is complicated by process chemosorbtion of dye on polymer for want of increased temperatures the process chemosorbtion is weakened also response comes nearer to the first order on dye. Is established, that the optimum environment, in which the process is carried conducted, is aceton.